Phospho-tau 181 is enhanced in saliva and plasma of edentulous patients: a first sign of dementia? - Zürcher, Christine; Defrancesco, Michaela; Humpel, Christian (Frontiers in Oral Health, 2025)
ObjectivesThere is evidence that periodontitis can enhance the progression of Alzheimer's disease (AD). The biomarkers beta-amyloid (40 and 42), total tau, and phospho-tau181 (pTau181) in cerebrospinal fluid help to diagnose AD. Saliva is an easy-to-collect fluid and we aim to analyze these biomarkers in patients with periodontitis.Subjects and methodsFour groups of individuals were included: patients with healthy periodont, those with mild and severe periodontal diseases, and edentulous patients. These four biomarkers were analyzed in saliva using Lumipulse technology, and as a control, also cortisol, transferrin, and interleukin-6 were measured. Patients underwent a neuropsychological assessment, and plasma pTau181 was analyzed.ResultsNo changes were seen for salivary beta-amyloid and total tau; however, salivary pTau181 was significantly increased in edentulous patients. This was accompanied by enhanced plasma pTau181 levels.ConclusionOur data show that pTau181 was significantly higher in saliva and plasma of edentulous patients, and we suggest that the loss of teeth may be linked to the progression of dementia. Consultation of dentists may be of importance to find risk factors for the progression of dementia, and salivary pTau181 could be a new associative marker.